Relationship between Knee Proprioception, Pain and_x000D_ Functıonality in Patients with Patellofemoral Pain_x000D_ Syndrome - (:unkn) unknown (My University, 2020)
Objective: This study aimed to evaluate the relationship between pain, functional level, and joint position sense in patellofemoral pain syndrome (PFPS).Material and Methods: In total, 20 healthy volunteers and 20 patients with PFPS who met the inclusion criteria were included in the study. The visual analog scale for pain assessment; Kujala patellofemoral score (KPS), and lower extremity functionality scale (LEFS) for functional assessment; step down, anteromedial lunge, and bilateral squat tests for clinical functional assessment; universal goniometer for knee joint angle; and digital goniometer for joint position sense of the knee joint were used.Results: When the evaluations were analyzed, statistically significant difference was found between KPS, LEFS (p=0.000; 0.000), clinical functional test measurements (p=0.000), and knee joint flexion angle (p=0.043). There was no statistically significant difference between the groups with respect to knee joint position sense values (p>0.05).Conclusion: Decreased functional levels in patients with PFPS were associated with increased pain intensity. However, there was no correlation between the measure of joint position sense and functional level and pain. Functional level was also affected in healthy extremities of patients with PFAS compared with the control group. We recommend that functionality of both the lower extremities be considered in rehabilitation programs to be implemented in PFPS.

Amaç: Bu çalışmanın amacı patellofemoral ağrı sendromu olan hastalarda ağrı, fonksiyonel seviye ve propriosepsiyon hissi arasındaki ilişkinin değerlendirilmesiydi._x000D_ Gereç ve Yöntem: Çalışmaya dahil edilme kriterlerine uyan 20 patellofemoral ağrı sendromu (PFAS) olan hasta ve 20 sağlıklı birey dahil edildi. Ağrı değerlendirmesi için “Vizüel Analog Skala (VAS)”, fonksiyonel değerlendirme için patellofemoral problemlere özel olarak geliştirilmiş “Kujala patellofemoral skorlaması” ve “Alt Ekstremite Fonksiyonellik Skalası”, klinik fonksiyonel değerlendirme için “basamak inme testi”, “anteromedial hamle testi” ve “bilateral çömelme testi”, diz ekleminin hareket açıklığı ölçümü için “universal gonyometre” ve diz ekleminin propriosepsiyon değerlendirmesi için “dijital gonyometre” kullanıldı._x000D_ Bulgular: Değerlendirmeler analiz edildiğinde iki grup arasında Kujala patellofemoral skorlaması, alt ekstremite fonksiyonellik skalası (p=0,000; 0,000), klinik fonksiyonel test ölçümleri (p=0,000) ve diz eklemi fleksiyon hareket açıklığı ölçümleri (p=0,043) arasında istatistiksel olarak anlamlı farklılık bulundu. Gruplar arasında diz propriosepsiyon ölçüm değerlerinde istatistiksel olarak anlamlı farklılık görülmedi (p>0,05)._x000D_ Sonuç: Patellofemoral ağrı sendromlu hastaların ağrı şiddetleri arttıkça fonksiyonel seviyelerinin azaldığı görülmüştür. Ancak propriosepsiyon değerleri ile fonksiyonel seviye ve ağrı arasında bir ilişki görülmemiştir. PFAS’lı hastaların sağlam ekstremitelerinde de fonksiyonel düzeyin kontrol grubuna göre etkilendiği belirlenmiştir. PFAS’da uygulanacak rehabilitasyon programlarında her iki alt ekstremite fonksiyonelliğinin göz önünde bulundurulmasını önermekteyiz.
Patellofemoral Ağrı Sendromu Olan Hastalarda Diz Propriosepsiyonu, Ağrı ve Fonksiyonellik Arasındaki İlişki